Anaplastic large cell (CD30/Ki-1+) lymphoma in HIV+ patients: clinical and pathological findings in a group of ten patients - Nosari, A; Cantoni, S; Oreste, P; Schiantarelli, C; Landonio, G; Alexiadis, S; Gargantini, L; Caggese, L; Gambacorta, M; Morra, E (British journal of haematology, 1996)
We compared the clinical and pathological features of 10 HIV+ CD30+ anaplastic large cell lymphoma (ALCL) patients with 28 HIV+ CD30- non-Hodgkin's lymphoma (NHL) patients. The incidence of ALCL among 38 HIV+ systemic NHL patients was 26%. Clinical features were similar in all the HIV-related NHL cases, but ALCL patients seemed to differ from HIV+ CD30- systemic NHL only in the greater frequency of lung tumours (40% v 21%) without concomitant mediastinal mass, bone marrow (75% v 18%) and gastroenteric involvement (40% v 25%). Among the HIV+ ALCL patients, histologic subtypes did not differ in frequency from ALCL in the general population. The B phenotype was predominant (50%) as in other HIV-related NHL. EBV genoma, studied in all HIV+ ALCL patients, was present in 3/10 by in situ hybridization (ISH) and in 5/10 cases using PCR. The clinical course of lymphomas was similar in CD30 positive and negative NHL patients. Overall survival also was short in our series, particularly in HIV+ ALCL (84 v 188 d), probably because of profound immunodepression of the ALCL patients. Our findings suggest that severe immunodepression due to HIV infection determines-more than any other factor-the clinical features of HIV+ ALCL, making them very similar to those of other high-grade systemic HIV+ NHL.